Is investing in apprentices related to decision-makers' altruism and their high time preference? - Jansen, Anika [Verfasser] (My University, 2016)
"In this article, the relation between firms' engagement in apprenticeship training and two important economic preferences, i.e. the decision makers' altruism and time preference, is analyzed. Firstly, the relation between these two preferences and a firms' decision to provide apprenticeship places (extensive margin) is examined. Secondly, for firms that train, the effect on the amount of investments in apprenticeship training (intensive margin) is analyzed. The results show that the degree of altruism of a decision maker is positively, albeit weakly significant, associated to the probability to provide apprenticeship places as well as substantially related to the amount of investments in apprenticeship training. Time preferences are not related to the training decision (extensive margin) but significantly related to the amount of investments in training." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; Ausbildungsinvestition; Betriebliche Berufsausbildung; Ausbildungsbetrieb; Ausbildungsverhalten; Ökonomische Faktoren